Estudo prospectivo de fatores preditivos de qualidade de vida em pacientes com câncer de colón e reto - Oliveira, Cristiano Pereira de (2015)
This Master’s research is composed of two empirical papers, the first one is a characterization of quality of life (QoL), physical and psychosocial factors in patients with Colorectal cancer (CRC). The second reference is to the identification of factors that can predict QoL in this population. The objectives that guided this thesis were to characterize patients with this cancer and to identify factors that predict QoL in patients with CRC . As a method carried out a longitudinal evaluation at baseline and at follow -up 51 patients elected for convenience and were assessed through self-report to QoL in addition to social demographic and clinical variables. On the other hand, if sought - diagnostic and therapeutic information in the medical records. After, there was descriptive and inferential statistics analysis establishing the necessary comparisons and correlations. The results identified a characteristic profile with relatively homogeneous distribution 51 % men with the middle age of 60.1 ( ±9,1) at baseline , as psychosocial aspects in general had higher QoL with other studies on the same population , and a significant improvement over time of all the subscales of performance and symptoms. Also shown that the physical aspects influence QoL. Concerning the predictors in this study there was no evidence links between gender and QoL, except for the initial assessment during chemotherapy indicating relationship between a man predicts to have more diarrhea. Another relevant fact is the relationship schooling, which have higher level indicates greater loss in appetite seconds findings at baseline. The presence of pain at follow -up can be correlated with the fact living alone. When considering the treatment protocols, FOLFIRI and Bevacizumab shown to be related to worse QoL. Also, if the trend showed a pain as a predictor of poor QoL. The relationship between self QoL l reporting among individuals who died and the survivors had minimum ratio indicating that they are independent. Regarding the presence of the mutated K-RAS gene the unique relationship was related with appetite loss. Finally, the symptoms of anxiety and depression were important predictors global QoL subscales and at follow-up. The main conclusion of the study findings is the need for multidisciplinary care that addresses the specific demands on this diagnosis.